Clofibric acid removal at activated carbon fibers by adsorption and electro-Fenton regeneration – Modeling and limiting phenomena. (20th June 2021) - Trellu, Clément; Gibert-Vilas, Màxim; Pechaud, Yoan; Oturan, Nihal; Oturan, Mehmet A.
Highlights: Clofibric acid adsorption on ACF and subsequent regeneration of spent ACF. Between 60 and 88% of regeneration yield. TOC lower than 1 mg L −1 in the solution at the end of the treatment. Proposition of a new model structure including sorption and reaction phenomena. Degradation in the solution is a crucial parameter for enhancing desorption. Abstract: The electro-Fenton process recently appeared as a promising technology for the regeneration of activated carbon (AC). The objective is to achieve both the regeneration of AC for further reuse and the mineralization of adsorbed pollutants. The use of AC fiber (ACF) presents several crucial advantages for this integrated strategy of treatment-regeneration, such as the fast adsorption kinetics and the suitability to use this material as cathode during the regeneration step. The results reported in this study showed that it is possible to achieve a regeneration yield between 60 and 88% depending on operating conditions (current intensity, treatment time, initial load of the AC) during the regeneration of ACF loaded with clofibric acid, an organochlorine compound. The TOC in the solution quickly decreased and reached a concentration lower than 1 mg L −1 at the end of the treatment. A new model structure was proposed, calibrated and validated with different operating conditions. This modeling work combined with a sensitivity analysis highlighted limiting phenomena as well as crucial parameters for regeneration effectiveness. Particularly, the kinetic parameter of the degradation of organic compounds in the solution appeared to be a critical parameter for promoting desorption of pollutants, particularly those that are not available for oxidation on ACF. Oxidation in the solution allows for shifting the sorption equilibrium, thus achieving a continuous desorption of organic compounds.